(untitled) (Research, Society and Development, 2020)
This work aims to reflect about Scientific Literacy (AC), investigating possible interactions of this theme between five general skills of the National Curricular Common Base (BNCC) in the scope of Basic Education. The qualitative methodology, through bibliographic research, allowed the authors to reflect on the theme, making a relation with the ideas of theorists that deal with Scientific Literacy. The AC is understood as a process that takes place inside and outside the school, implying the generation of dialogues and shortening the distance between the subjects’ experiential culture and scientific knowledge. The AC is also capable of promoting the necessary conditions to carry out critical readings and interpretations of reality, being an invitation to participate in the community debate, providing people with the aptitude for conscious and responsible decision-making, which can bring interventions to the space where the subject if inserted. The discussion points out the competences: Knowledge; Scientific, Critical and Creative Thinking; Argumentation; Responsibility and Citizenship, as possibilities for developing AC for students. Since these competences assist in the development of the individual’s argumentative capacity in relation to the environment that surrounds him. In addition to understanding the possibilities of implementing Scientific Literacy, it is convenient to think about the need for investments and structural equipment in schools, which can help in the development and expansion of AC in the social environment.